A web based software tool for business management - Lim, Sherman Kwang Hwee (Nanyang Technological University, 2022)
This report is for a final year project on building a web application named BizApp using Java language. BizApp is a web-based application that function as an administrative and communication tool to aid small business in boosting their productivity. This report describes the current issues faced by new owners of small business. Existing solutions in the market are not ideal, which motivates the project to build a business management tool targeted for small business. The report includes an overview of open-source software, which provides the benefits and advantages that can be applied for the development of the BizApp. To ensure BizApp is an effective solution, system and functional requirements are first specified before the features and implementation of BizApp is described. The entire development process of BizApp from design to deployment is detailed. BizApp consists of nine functions including task assignment to employees, form submission for leave of absence, shared calendar for manpower allocation, contact list of employees, customers, and suppliers, tracking of purchase orders and inventory, issuing invoice to customers, sales performance monitoring and access control for security. Upon completing the development process, testing was carried out and the results are presented with illustrations of the functionalities of BizApp. The report is concluded with a reflection with problems encountered during the development of BizApp and the alternative solutions taken to resolve the issues. Recommendations to further enhance BizApp in the future are also provided.